Increasing prevalence of hypertension during long-term follow-up in children with autosomal dominant polycystic kidney disease - Seeman, Tomáš; Jansky, Petr; Filip, Fencl; Bláhová, Květa; Jaroš, Adam (Pediatric nephrology (Berlin, Germany), 2021)
INTRODUCTION: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease. Kidney cysts form over the course of the disease and kidney function slowly declines, usually leading to kidney failure in middle to late adulthood. However, some symptoms, such as hypertension or proteinuria, can be present at an earlier age. In this study, we aimed to quantify early complications in children over time. METHODS: All 69 children with ADPKD from our pediatric nephrology center who met inclusion criteria (follow-up ≥ 1 year and ≥ 2 recorded visits) were studied. Analysis of changes in kidney size, cyst count, estimated glomerular filtration rate (eGFR), urinary protein excretion, and blood pressure was performed. RESULTS: The median time of follow-up was 6.3 years (range 8.4-14.8). Over the follow-up, kidneys grew from 109 to 115% of expected length (p < 0.0001), number of cysts increased at a rate of 0.8 cyst/kidney/year, and the prevalence of hypertension increased significantly from 20 to 38% (p < 0.015). The eGFR and absolute urinary protein excretion remained stable. CONCLUSIONS: This study shows that children with ADPKD suffer from increasing prevalence of hypertension during the course of the disease parallel to the increasing number of kidney cysts and size despite normal and stable kidney function and proteinuria. A higher resolution version of the Graphical abstract is available as Supplementary information.
Keywords: Hypertension; dítě; Glomerular filtration rate; Polycystic Kidney, Autosomal Dominant; lidé; prevalence; Children; Follow-Up Studies; hypertenze; Humans; Proteinuria; následné studie; Autosomal dominant polycystic kidney disease; Prevalence; polycystické ledviny autozomálně dominantní; Child